Micro-Financing's Role in Alleviating Poverty – A Critical Review - Vijay Kumar (International Journal of Modern Agriculture, 2020)
In rural and urban India, as in various parts of the world, micro-financing has been instrumental in alleviating poverty. In terms of their socio-economic empowerment and healthy livelihoods founded on dignity and self-respect, this paper offers an overview of how micro-financing has changed the lives of the poor. In order to decode the effect of micro-financing on poverty alleviation, especially in the Indian context , the author has examined a number of conceptual and empirical studies. As a holistic intervention technique in the contemporary development model, the paper provides an incisive criticism of micro-financing.